Financial Literacy on PayLater for College Students to Prevent Compulsive Spending - Rita Nurnaningsih; Irzan Soepriyadi; Dipa Teruna Awaludin; Meike Negawati Kesek; Kampono Imam Yulianto (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
Advances in financial technology have introduced a variety of digital payment services that are increasingly accessible to the public, including the PayLater feature. The convenience offered by this service provides benefits in supporting flexible financial transactions. However, on the other hand, the use of PayLater without adequate financial literacy has the potential to encourage excessive spending, particularly among college students who are in the transition phase toward financial independence. Therefore, this community service activity aims to enhance students’ understanding of the prudent use of PayLater, introduce the risks that may arise from uncontrolled use, and foster awareness of the importance of personal financial management. The activity was conducted online using an interactive educational method that included material delivery, discussions, case studies, and an evaluation of participants’ understanding. The material covered the basic concepts of PayLater, the benefits and risks of its use, its impact on consumerist behavior, and strategies for healthy financial management. The results of the activity showed an increase in participants’ understanding of responsible PayLater usage and the importance of considering financial capacity before making transactions. Additionally, participants demonstrated a shift in perception regarding the use of digital credit services, placing greater emphasis on needs rather than wants.